Thymoma With Pure Red Cell Aplasia and Good's Syndrome - Chen, Jun; Yang, Yongbo; Zhu, Daxing; Chen, Gang; Wei, Sen; Qiu, Xiaoming; Zhou, Qinghua (The Annals of thoracic surgery, 2011)
Thymoma patients with pure red cell aplasia (PRCA) or hypogammaglobulinemia (Good's syndrome) are rare, whereas those with both PRCA and Good's syndrome are even rarer. Here we present the case report of a 70-year-old woman with invasive thymoma and simultaneous PRCA and Good's syndrome, who achieved complete PRCA remission after thymectomy.